2019
DOI: 10.1111/cyt.12677
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor‐II mRNA‐binding protein 3 immunocytochemical expression in direct endometrial brushings: Possible diagnostic help in endometrial cytology

Abstract: IntroductionThis study evaluated the immunocytochemical (ICC) expression of IMP3 in direct endometrial brushings processed as liquid‐based cytology (LBC) samples of endometrioid adenocarcinoma (EAC), serous carcinoma (ESC) and surface papillary syncytial change (SPSC) with endometrial glandular and stromal breakdown (EGBD) to exploit its possible differential diagnostic aid.MethodsIn total, 333 samples of LBC samples were obtained from selected outpatients in parallel with Pipelle endometrial sampling. They co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Unfortunately, cytological diagnosis of endometrial brushings is frequently hampered by the presence of benign endometrial lesions (eg reactive or metaplastic changes), masking or mimicking a malignancy. In particular, SPSC is frequently observed in association with EGBD, a relatively common clinical manifestation necessitating endometrial cytological examination in several patients; furthermore, it may be detected in abnormal endometrial conditions such as polyps and hyperplasias, and even in biopsies of EC obtained during metrorrhagia 11‐13,20 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, cytological diagnosis of endometrial brushings is frequently hampered by the presence of benign endometrial lesions (eg reactive or metaplastic changes), masking or mimicking a malignancy. In particular, SPSC is frequently observed in association with EGBD, a relatively common clinical manifestation necessitating endometrial cytological examination in several patients; furthermore, it may be detected in abnormal endometrial conditions such as polyps and hyperplasias, and even in biopsies of EC obtained during metrorrhagia 11‐13,20 …”
Section: Discussionmentioning
confidence: 99%
“…In particular, SPSC is frequently observed in association with EGBD, a relatively common clinical manifestation necessitating endometrial cytological examination in several patients; furthermore, it may be detected in abnormal endometrial conditions such as polyps and hyperplasias, and even in biopsies of EC obtained during metrorrhagia. [11][12][13]20 Additionally, as SPSC may occasionally display papillary architecture and a degree of nuclear atypia resembling ESC (including its precursor lesion), it may be misdiagnosed as a malignancy (Figures 2 and 3). 21,22 Hence, the cytological distinction between a benign endometrium and a malignant one is of critical significance given the subsequent triage (e.g.…”
Section: Differential Diagnosis Between Ec (G1-eec G3-eec and Esc)mentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors [65][66][67][68] reported that "insulinlike growth factor-II mRNA-binding protein 3 (IMP3)" is a useful ICC marker to distinguish between ESC and EAC (G1, G3). Very recently, Norimatsu et al [69] also found that IMP3 is one of the helpful ICC markers to distinguish ESC from EAC (G1, G3) or MCIP. When the score ≥3 threshold for positivity of IMP3 ICC expression was used, only ESC cases showed significantly higher expression than EAC (G1, G3) cases, while all of the benign endometrium cases including MCIP showed negative cytoplasmic staining.…”
Section: Discrimination Between Egbd and Ecmentioning
confidence: 98%